Optical properties, spectral, and lifetime measurements of central nervous system tumors in humans. Issue 1 (December 2017) - Poulon, F.; Mehidine, H.; Juchaux, M.; Varlet, P.; Devaux, B.; Pallud, J.; Abi Haidar, D.
Abstract A key challenge of central nervous system tumor surgery is to discriminate between brain regions infiltrated by tumor cells and surrounding healthy tissue. Although monitoring of autofluorescence could potentially be an efficient way to provide reliable information for these regions, we found little information on this subject, and thus we conducted studies of brain tissue optical properties. This particular study focuses on the different optical quantitative responses of human central nervous system tumors and their corresponding controls. Measurements were performed on different fixed human tumoral and healthy brain samples. Four groups of central nervous system tumors (glioblastoma, diffuse glioma, meningioma and metastasis) were discriminated from healthy brain and meninx control tissues. A threshold value was found for the scattering and absorption coefficient between tumoral and healthy groups. Emission Spectra of healthy tissue had a significant higher intensity than tumoral groups. The redox and optical index ratio were thenn calculated and these also showed significant discrimination. Two fluorescent molecules, NADH and porphyrins, showed distinct lifetim values among the different groups of samples. This study defines several optical indexes that can act as combinated indicators to discriminate healthy from tumoral tissues.